THE EFFECT OF GENDER, AGE, AND SYMPTOM SEVERITY IN LATE-LIFE DEPRESSION ON THE RISK OF ALL-CAUSE MORTALITY: THE BAMBUÍ COHORT STUDY OF AGING - Diniz, Breno S.; Reynolds III, Charles F.; Butters, Meryl A.; Dew, Mary Amanda; Firmo, Josélia O. A.; Lima-Costa, Maria Fernanda; Castro-Costa, Erico (Depression and anxiety, 2014)
Background Increased mortality risk and its moderators is an important, but still under recognized, negative outcome of late‐life depression (LLD). Therefore, we aimed to evaluate whether LLD is a risk factor for all‐cause mortality in a population‐based study with over 10 years of follow‐up, and addressed the moderating effect of gender and symptom severity on mortality risk. Methods This analysis used data from the Bambuí Cohort Study of Aging. The study population comprised 1.508 (86.5%) of all eligible 1.742 elderly residents. Depressive symptoms were annually evaluated by the GHQ‐12, with scores of five or higher indicating clinically significant depression. From 1997 to 2007, 441 participants died during 10,648 person‐years of follow‐up. We estimated the hazard ratio for mortality risk by Cox regression analyses. Results Depressive symptoms were a risk factor for all‐cause mortality after adjusting for confounding lifestyle and clinical factors (adjusted HR = 1.24 CI95% [1.00–1.55], P = .05). Mortality risk was significantly elevated in men (adjusted HR = 1.45 CI95% [1.01–2.07], P = 0.04), but not in women (adjusted HR = 1.13 CI95% [0.84–1.48], P = 0.15). We observed a significant interaction between gender and depressive symptoms on mortality risk ((HR = 1.72 CI95% [1.18–2.49], P = 0.004). Conclusion The present study provides evidence that LLD is a risk factor for all‐cause mortality in the elderly, especially in men. The prevention and adequate treatment of LLD may help to reduce premature disability and death among elders with depressive symptoms.